The Urgency of Registering Industrial Design Intellectual Property Rights as an Effort to Increase Competitiveness in the Global Era - Alamanda, Asri Elies; Mutmainah, Lailatul (LEGAL BRIEF, 2024)
Registration of Intellectual Property Rights (IPR) for industrial designs is a crucial step in increasing product competitiveness in the global era. In the midst of increasingly fierce competition, protection of innovative designs is important to maintain the uniqueness and added value of products. IPR registration not only provides legal protection for designs, but also improves the company's image and reputation, and encourages innovation. In addition, IPR owners can take advantage of exclusive rights to explore new business opportunities and improve their bargaining position in the global market. The method used in this study is the normative research method. It is important for industry players to understand and utilize IPR registration as a primary strategy in facing the challenges of a dynamic global market. This study aims to explore the urgency of industrial design IPR registration and its impact on industrial competitiveness, as well as provide recommendations for industry players in maximizing the potential of IPR as a strategic asset. Government policies have an important role in supporting and facilitating the industrial design registration process to increase the competitiveness of local products in the international market. Industrial design registration provides legal security for design owners in running their businesses. With the legal protection provided by the Industrial Design Law, design owners can be more confident in doing business, investing in the development of new designs, and establishing business partnerships without fear of imitation or copyright infringement